CD39(+) regulatory T cells accumulate in colon adenocarcinomas and display markers of increased suppressive function - Ahlmanner, Filip (Oncotarget, 2018)
Increasing knowledge of the function and regulation of tumor-infiltrating lymphocytes has led to new insights in cancer immunotherapy. Regulatory T cells (Treg) accumulate in colon tumors, and we recently showed that CD39(+) Treg from cancer patients inhibit transendothelial migration of conventional T cells. CD39 mediates the hydrolysis of ATP to immunosuppressive adenosine and adds to the immunosuppressive effects of Treg. Here, we further investigated the regulatory features of intratumoral CD39(+) Treg in colon cancer. Using flow cytometry analyses of cells from 46 colon cancer patients, we confirm the accumulation of CD39(+) Treg in the tumor tissue compared to unaffected colon tissue, and also show that tumor-infiltrating Treg express more CD39 and Foxp3 on a per cell basis. Furthermore, CD39(+) Treg in tumors express markers indicating increased turnover and suppressive ability. In particular, tumor-infiltrating CD39(+) Treg have high expression of surface molecules related to immunosuppression, such as ICOS, PD-L1 and CTLA-4. Functional suppression assays also indicate potent suppressive capacity of CD39(+) Treg on proliferation and IFN-γ secretion by conventional T cells. In conclusion, our results identify tumor-infiltrating CD39(+) Treg as a numerous and potentially important immunosuppressive subset, and suggest that immunotherapy aimed at reducing the activity of CD39(+) Treg may be particularly useful in the setting of colon cancer.